THE USE OF POLICE DISCRETION IN INVESTIGATIONS OF CRIME IN THE MINING SECTOR - Kadek Agus Surya Darma; Lesza Leonardo Lombok; Feibe Engeline Pijoh (International Journal of Applied Science and Sustainable Development (IJASSD), 2025)
Criminal acts in the mineral mining sector in Indonesia are rife and have become public knowledge. These criminal acts include mining without a mining business permit, data manipulation practices at the exploration stage, mining in protected forest areas, limited production forests and laundering of mining products as well as reclamation and post-mining. The police play a very important role in carrying out law enforcement duties in the environmental sector. Sometimes, because of the lack of environmental knowledge, the police use discretion. Although acting based on the law is basically considered to be contrary to the granting of discretion to the Police, discretion, on the one hand, is considered to eliminate certain predictions regarding the results that will be obtained, but, on the other hand, it also ensures that the principle of legal certainty is maintained, which is wrong an important aspect of law. By using normative legal method, this research aims to find out the reasons behind the police's decision to use discretion in mining criminal cases, and to discover the implementation of Police discretion in the process of investigating criminal acts in the mining sector in Indonesia. The author finds that various factors influence the use of discretion by the Police, including the seriousness of criminal acts, availability of resources, environmental impacts, and the interests of the community and other stakeholders. Based on the context of law enforcement in the mining sector in Indonesia, the implementation of discretion by the Police includes various forms of approaches that are appropriate to the complexity and challenges faced. Several forms of discretion applied by the Police in the process of investigating mining crimes in Indonesia include determining case priorities in handling cases of mining crimes.